Risk Factors for Granulocytopenia in Patients with Graves’ Disease Receiving Antithyroid Drugs - Jiaxi Li; Xiaowen Zhang; Lintong Li; Qiaoling Zhu; Weihong Ge; Cheng Ji (International Journal of Endocrinology)
Objective. To study the risk factors for granulocytopenia caused by antithyroid drugs. Methods. Patients who were diagnosed with Graves’ hyperthyroidism and regularly treated with antithyroid drugs (ATDs) from January 2010 to July 2022 at Nanjing Drum Tower Hospital, aged >18 years, were selected for general information and laboratory tests and divided into two groups according to the occurrence of granulocytopenia. Independent risk factors for the development of granulocytopenia in patients treated with ATDs were analyzed using one-way and multiway logistic regression analyses, and the predictive value of each index was evaluated using the receiver operating characteristic (ROC) curve and the area under the curve (AUC). Results. A total of 818 patients were enrolled, of which 95 developed granulocytopenia. Univariate analysis revealed that sex, white blood cell (WBC) counts, neutrophil-to-lymphocyte ratio (NLR), glutamic-pyruvic transaminase (ALT), aspartate transaminase (AST), free triiodothyronine (FT3), free thyroxine (FT4), and thyroid stimulating hormone (TSH) before medication were risk factors for ATD-induced granulocytopenia (P<0.05). The abovementioned indicators were taken as independent variables, and multivariate logistic regression analysis showed that female sex, higher ALT levels before medication, and lower NLR and WBC levels were independent risk factors for granulocytopenia using ATDs (P<0.05). ROC curve analysis showed that sex, NLR, ALT, and WBC count had significant predictive values (P<0.05), and NLR and WBC count had higher predictive values (AUC = 0.916 and 0.700, respectively). Conclusion. Sex, NLR, ALT, and WBC were the main risk factors for granulocytopenia in patients with ATD.